Are urban visitors’ general preferences for green-spaces similar to their preferences when seeking stress relief? - Arnberger, Arne; Eder, Renate (Urban forestry & urban greening, 2015)
•Urban green-space visitors’ general preferences for green-space characteristics are similar to their site preferences when seeking stress relief.•For stress relief respondents placed more importance on visitor numbers.•Litter and trail environment played a larger role in general preferences.•User conflicts and crowding seem to play a more important role for stated stress-relief preferences.•The stress-relief preferences of respondents did not differ remarkably subject to their own reported stress level. Many urban societies are faced with a growing incidence of poor health because of mental stress and sedentary lifestyles. Urban green spaces are increasingly seen as a counter to hectic city living and as restorative settings. This study investigates the preferences for site characteristics green-space visitors have when they are seeking stress relief compared to their general green-space preferences. This study developed a conceptual framework integrating physical and social characteristics of different green-space types in Vienna, Austria and investigated the preferences of 692 on-site visitors. A stated choice model with digitally calibrated images found that visitors’ general preferences are similar to their site preferences when seeking stress relief. However, for stress relief, visitor numbers played a more important role in their green-space choices, while litter and trail environment played a larger role in general preferences. The stress-relief preferences of respondents did not differ remarkably subject to their own reported stress level. Recommendations for green-space planning are derived.